The role of calcium-calpain pathway in hyperthermia - Enomoto, Atsushi; Fukasawa, Takemichi (Frontiers in Molecular Medicine, 2022)
Hyperthermia is a promising anticancer treatment modality. Heat stress stimulates proteolytic machineries to regulate cellular homeostasis. Calpain, an intracellular calcium (Ca2+)-dependent cysteine protease, is a modulator that governs various cellular functions. Hyperthermia induces an increase in cytosolic Ca2+ levels and triggers calpain activation. Contrastingly, pre-exposure of cells to mild hyperthermia induces thermotolerance due to the presence of cellular homeostatic processes such as heat shock response and autophagy. Recent studies suggest that calpain is a potential key molecule that links autophagy and apoptosis. In this review, we briefly introduce the regulation of intracellular Ca2+ homeostasis, basic features of calpains with their implications in cancer, immune responses, and the roles and cross-talk of calpains in cellular protection and cell death in hyperthermia.